Correlation of the mediterranean diet with some diseases - Adriatik Jahjaga Daniela Shukova Stojmanovska Seryozha Gontarev Georgi Georgiev (Physical Education and Sport Faculty, 2022)
The research was conducted on 38 respondents in total, at the age from 40 to 80 years, grouped as follows: 14 with cerebral tumor, 12 with cardiac ischemia and 12 with colon cancer, who were hospitalized in the University clinical center in Pristine. Five variables were applied during the research: age, height, weight, daily number of smoked cigarettes and KIDMED Index, collected by a questionnaire. BMI (Body Mass Index) was calculated from the height (Height) and the body mass (Weight). The KIDMED questionnaire consists of 16 questions (each having a positive or negative point) that are related to the eating of particular food-types incorporated in the Mediterranean diet. Through summing the points, the so called Index of Mediterranean diet (KIDMED Index) can be obtained, and if the KIDMED Index has the values of ≤ 3, it indicates a low degree and is a mark of little use of the Mediterranean diet, optimal values are 4-7 and it is high with the values of ≥ 8. Along with the descriptive statistical parameters, the following analyses were calculated, too, for each of the applied variables: multivariate analysis of variance (MANOVA), one-factor univariate analysis of variance (ANOVA), post-hoc analysis, contingency tables based on the χ 2 test values and contingency coefficients as well as testing their differences. On grounds of the performed research, it can be stated that the group with cardiac ischemic disease is that of the youngest persons whose average age is 50 years at the time when the disease occurred and the oldest of the respondents-those of 64 years-are the patients diagnosed with colon cancer. Regarding the KIDMED Index, there are statistically significant differences between the groups of different diagnoses (patients diagnosed with cerebral tumor, cardiac ischemia and colon cancer). It is established that the group diagnosed with cerebral tumor has the largest number of patients with a low KIDMED Index (28,6%). Persons of that group have the greatest daily number of smoked cigarettes (H= 7,14) and have in average the highest BMI = 28, which indicates excessive body mass. Although 50% of the cardiac ischemic disease patients have high and optimal KIDMED Index (same percentage in each), yet these patients are the youngest of all three groups. It means that there might be another factor that causes the "inadequate early" strikes of the disease.